The Role of Autophagy in Critical Illness-induced Liver Damage. Issue 1 (December 2017) - Thiessen, Steven; Derese, Inge; Derde, Sarah; Dufour, Thomas; Pauwels, Lies; Bekhuis, Youri; Pintelon, Isabel; Martinet, Wim; Van den Berghe, Greet; Vanhorebeek, Ilse
Abstract Mitochondrial dysfunction and endoplasmic reticulum (ER) stress, which activates the unfolded protein response (UPR), mediate critical illness-induced organ failure, often affecting the liver. Autophagy is known to alleviate both and suppressed or insufficiently activated autophagy in prolonged illness has shown to associate with organ failure. Whether insufficient autophagy contributes to organ failure during critical illness by affecting these underlying mechanisms is incompletely understood. In this study, we investigated whether the inability to acutely activate hepatic autophagy during critical illness aggravates liver damage by increasing hepatic mitochondrial dysfunction and affecting the UPR. In a mouse model of critical illness, induced by surgery and sepsis, we investigated the impact of inactivating hepatic autophagy on markers of hepatic mitochondrial function, the UPR and liver damage in acute (1 day) and prolonged (3 days) critical illness. Hepatic autophagy inactivation during critical illness acutely worsened mitochondrial dysfunction and time-dependently modulated the hepatic UPR. Furthermore, autophagy inactivation aggravated markers of liver damage on both time points. In conclusion, the inability to acutely activate autophagy in liver during critical illness worsened hepatic mitochondrial damage and dysfunction, partially prohibited acute UPR activation and aggravated liver damage, indicating that autophagy is crucial in alleviating critical illness-induced organ failure.